Tumor‐Derived Peptidoglycan Recognition Protein 2 Predicts Survival and Antitumor Immune Responses in Hepatocellular Carcinoma. Issue 5 (24th January 2020) - Yang, Zongyi; Feng, Jia; Xiao, Li; Chen, Xi; Yao, Yuanfei; Li, Yiqun; Tang, Yu; Zhang, Shuai; Lu, Min; Qian, Yu; Wu, Hongjin; Shi, Ming
Abstract : Background and Aims: Hepatocellular carcinoma (HCC) is linked to immunosuppression. Relieving immunosuppression has been an attractive strategy to improve the efficacy of cancer immunotherapy. Peptidoglycan recognition protein 2 (PGLYRP2) is a pattern recognition receptor which is specifically expressed in liver and implicated in the regulation of innate immunity and immunosurveillance. However, the role of hepatic PGLYRP2 in modulating immune responses against HCC remains to be investigated. Approach and Results: In this study, we investigated whether PGLYRP2 is able to influence HCC progression through regulating host antitumor immune responses. We demonstrated that PGLYRP2 was down‐regulated in HCC, which was linked with poor prognosis in patients ( P  < 0.001). PGLYRP2 overexpression in HCC cells significantly enhanced antitumor immune responses in immune‐competent mice and elevated immune response rates of peripheral blood mononuclear cells against HCC . Mechanistically, DNA methyltransferase 3A–mediated promoter hypermethylation was responsible for the down‐regulation of PGLYRP2 in HCC. PGLYRP2 promoted production of chemokine (C‐C motif) ligand 5 (CCL5) in HCC through binding to the CCL5 promoter, which contributed to the enhanced antitumor immunity. Conclusions: We provide evidence that tumor‐derived PGLYRP2 acts as a candidate biomarker for adequate immune response against HCC and improved patient outcomes, indicating the importance of hepatic PGLYRP2 in cancer immunosurveillance and in designing immunotherapeutic approaches.